Anti-adhesion agent composition for unvulcanized rubber and use thereof
Patent Information
- Application Number
- JP2023140867
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-31
- Publication Date
- 2025-03-13
AI Technical Summary
【0010】 本発明の未加硫ゴム用防着剤は乾燥性及び防着性に優れる。 本発明の防着処理された未加硫ゴムの製造方法は、上記未加硫ゴム用防着剤を未加硫ゴムの表面に付着させる工程を含むため、防着性に優れた未加硫ゴムの生産性に優れる。
Smart Images

Figure 2025034475000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an anti-adhesive composition for unvulcanized rubber and use thereof. [Background technology]
[0002] In the production and processing of rubber products, unvulcanized rubber is sometimes stored in piles until it is moved to the next process such as molding or vulcanization. In this case, adhesion inhibitors (anti-adhesion agents) are used to prevent the rubber pieces from sticking together. Conventionally, inorganic particles such as talc, mica, calcium carbonate, magnesium carbonate, and bentonite have been used as anti-adhesive agents because of their excellent anti-adhesive properties. One method of using them is the so-called wet method, which involves suspending powder of the inorganic particles in water and spraying the suspension, spraying the rubber with a thin stream, or immersing the rubber in the suspension. In the wet method, water is used not only to improve workability but also to cool the rubber.
[0003] Such anti-adhesive agents using inorganic particles can provide excellent anti-adhesive properties by completely drying after adhering to rubber using the wet method. However, if the concentration of the suspension is too high, the drying property decreases rapidly, and the rubber may be stacked and stored in a semi-dried state. In such a case, adhesion between rubbers may occur at the semi-dried portions. As a countermeasure, an anti-adhesive agent that does not use inorganic particles and is mainly made of organic matter has been developed. However, although this anti-adhesive agent has excellent wettability and drying properties, it has a problem that it is inferior in anti-adhesive properties to anti-adhesive agents that use inorganic particles.
[0004] Patent Document 1 discloses a method for preventing adhesion by applying a composition consisting of a specific ratio of a water-soluble polymer, a surfactant, and organic particles dispersed in water to unvulcanized rubber. Patent Document 2 discloses a method for preventing adhesion by treating unvulcanized rubber with a composition consisting of a specific ratio of a water-soluble polymer, water-insoluble organic polymer particles, a metal soap, a surfactant, and water. Both are adhesion-preventive compositions that use water-soluble polymers, and when the adhesion-preventive liquid applied to the rubber dries completely, they show excellent adhesion prevention. However, if the concentration of the treatment liquid used to prevent adhesion of unvulcanized rubber is high, the viscosity and water retention of the water-soluble polymers will cause a significant decrease in drying properties, and adhesion between rubber members may occur due to semi-drying. For this reason, there is a demand for the development of an anti-adhesive agent that has excellent anti-adhesive properties and drying properties. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2009-161667 A [Patent Document 2] International Publication No. 2018 / 030395 Summary of the Invention [Problem to be solved by the invention]
[0006] An object of the present invention is to provide an adhesion-preventive composition for unvulcanized rubber which is excellent in drying properties and adhesion prevention, and a method for producing unvulcanized rubber which has been treated for adhesion prevention with the adhesion-preventive composition for unvulcanized rubber. [Means for solving the problem]
[0007] As a result of intensive research to solve the above-mentioned problems, the present inventors have found that the above-mentioned problems can be solved by an anti-adhesive composition for unvulcanized rubber that contains specific components and satisfies specific conditions, and have arrived at the present invention. That is, the present invention relates to an anti-adhesive composition for unvulcanized rubber, which comprises the following components (A) to (C) and satisfies the following condition 1. Component (A): Wax Ingredient (B): Metal soap Component (C): Anionic surfactant Condition 1: The content of the component (A) and the content of the component (B) satisfy the relationship represented by the following formula (I). Content of component (A) < Content of component (B) (I)
[0008] It is preferable that the anti-adhesive composition for unvulcanized rubber of the present invention satisfies at least one of the following 1) to 3). 1) The total weight ratio of the components (A) to (C) to the non-volatile content of the adhesion preventive composition for unvulcanized rubber is 30% by weight or more. 2) The weight ratio of the component (A) to the non-volatile content of the adhesion preventive composition for unvulcanized rubber is 0.5 to 49% by weight, the weight ratio of the component (B) to 2 to 60% by weight, and the weight ratio of the component (C) to 1 to 70% by weight. 3) The component (C) contains a fatty acid salt.
[0009] The method for producing adhesion-preventively treated unvulcanized rubber of the present invention includes a step of adhering the above-mentioned adhesion-preventive composition for unvulcanized rubber to the surface of molded unvulcanized rubber. Effect of the Invention
[0010] The anti-adhesive agent for unvulcanized rubber of the present invention is excellent in drying property and anti-adhesive property. The method for producing adhesion-preventively treated unvulcanized rubber of the present invention includes a step of adhering the adhesion-preventive agent for unvulcanized rubber to the surface of unvulcanized rubber, and therefore is excellent in productivity of unvulcanized rubber with excellent adhesion prevention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The anti-adhesive composition for unvulcanized rubber (hereinafter, sometimes simply referred to as an anti-adhesive composition) of the present invention contains the following components (A) to (C). Component (A): Wax Ingredient (B): Metal soap Component (C): Anionic surfactant First, each component contained in the anti-adhesive composition of the present invention will be described, and then the anti-adhesive composition will be described in detail.
[0012] [Component (A)] The anti-adhesive composition of the present invention contains a wax as component (A), which is a component that imparts conformability to deformation to the anti-adhesive coating obtained when the anti-adhesive treatment is carried out, thereby imparting anti-adhesive properties. Examples of the component (A) include hydrogenated wax, vegetable wax, animal wax, mineral wax, petroleum wax, synthetic hydrocarbon wax, modified wax, fatty acid amide, and phthalic anhydride imide. The hydrogenated wax is not particularly limited, but examples thereof include hydrogenated waxes of hydrogenated castor oil, 12-hydroxystearic acid, derivatives of 12-hydroxystearic acid, lauric acid, myristic acid, palmitic acid, behenic acid, sebacic acid, undecylenic acid, heptyl acid, maleic acid, and the like, and one or more of these may be used in combination. Hydrogenated castor oil is a hard, brittle, white, high-melting wax obtained by hydrogenating castor oil, and is also called castor wax, pearl wax, etc. The main component of hydrogenated castor oil is glycerin tri-12-hydroxystearate, containing small amounts of mixed glycerides of 12-hydroxystearic acid, dihydroxystearic acid, and stearic acid.
[0013] The vegetable wax is not particularly limited, but examples thereof include candelilla wax, carnauba wax, rice wax, Japan wax, cheek oil, sugar wax, bayberry wax, oculi wax, esparto wax, etc., and one or more types may be used in combination. The animal wax is not particularly limited, but examples thereof include beeswax, lanolin, spermaceti, insect wax, shellac wax, etc., and one or more of these may be used in combination. The mineral wax is not particularly limited, but examples thereof include montan wax, ozokerite, ceresin, etc., and one or more of these may be used in combination.
[0014] The petroleum wax is not particularly limited, but examples thereof include paraffin wax, microcrystalline wax, petrolatum, etc., and one or more of these may be used in combination. The synthetic hydrocarbon wax is not particularly limited, but examples thereof include Fischer-Tropsch wax, polyethylene wax, and modified polyethylene waxes such as oxidized polyethylene wax and acid-modified polyethylene wax. One or more of these may be used in combination. The modified wax is not particularly limited, and examples thereof include montan wax derivatives, paraffin wax derivatives, and microcrystalline wax derivatives, and one or more of these may be used in combination. The fatty acid amide is not particularly limited, but examples thereof include lauric acid amide, stearic acid amide, oleic acid amide, erucic acid amide, N,N'-xylylenebisstearic acid amide, coconut oil fatty acid monoethanolamide, N-oleylstearic acid amide, N,N'-dioleyladipic acid amide, and the like, and one or more of these may be used in combination.
[0015] Component (A) is not particularly limited, but is preferably at least one selected from vegetable waxes, animal waxes, petroleum waxes, and synthetic hydrocarbon waxes in terms of achieving the effects of the present application, and is more preferably at least one selected from vegetable waxes, paraffin waxes, microcrystalline waxes, Fischer-Tropsch waxes, polyethylene waxes, and modified polyethylene waxes.
[0016] The melting point of component (A) is not particularly limited, but is preferably 60 to 150°C. If the melting point is 60°C or higher, a coating with excellent adhesion resistance tends to be formed on the surface of the unvulcanized rubber, and if the melting point is 150°C or lower, the resulting coating does not become too hard and tends to have improved conformability. The lower limit of the melting point is more preferably 70°C, and even more preferably 80°C. On the other hand, the upper limit of the melting point is more preferably 140°C, even more preferably 135°C, and particularly preferably 130°C.
[0017] Component (A) may be in a particulate form. When component (A) is in a particulate form, adhesion prevention tends to be improved, which is preferable. When component (A) is particulate, its volume average particle diameter is not particularly limited, but is preferably 0.1 to 10 μm. When the volume average particle diameter is within the above range, the amount of component (A) attached to the surface of the unvulcanized rubber increases, and adhesion prevention tends to improve. The lower limit of the volume average particle diameter is more preferably 0.12 μm, and even more preferably 0.15 μm. On the other hand, the upper limit of the volume average particle diameter is more preferably 5 μm, even more preferably 3 μm, and particularly preferably 1 μm. The volume average particle diameter means the volume-based D50 value measured by a laser diffraction scattering type particle size distribution measuring device (for example, LA-950 manufactured by Horiba, Ltd.).
[0018] When component (A) is a granular material, component (A) may be dispersed in a liquid dispersion medium such as water in the form of an emulsion or slurry when producing the adhesion-preventive composition. The water contained in the emulsion or slurry of component (A) corresponds to the water contained in the adhesion-preventive composition described below.
[0019] [Component (B)] The anti-adhesive composition of the present invention contains a metal soap as component (B), which is a component that imparts lubricity, anti-adhesive properties, and drying properties. Component (B) is not particularly limited, but may be a non-alkali metal salt of an organic acid having 10 to 20 carbon atoms, and is preferably a non-alkali metal salt of an organic acid having 10 to 18 carbon atoms. These non-alkali metal salts that are metal soaps may be used alone or in combination of two or more kinds.
[0020] The organic acid constituting the metal soap is not particularly limited, but may be one or more selected from capric acid, lauric acid, myristic acid, palmitic acid, palmitoleic acid, stearic acid, oleic acid and arachic acid. The non-alkali metal salt is not particularly limited, but may be composed of one or more of elements selected from Al, Ag, Ba, Ca, Ce, Cd, Co, Cr, Cu, Fe, Hg, Mg, Mn, Ni, Pb, Sn, Th, Ti, and Zn.
[0021] Component (B) may be in a particulate form, which is preferable in terms of improving lubricity. When component (B) is particulate, its average particle size is not particularly limited, but is preferably 0.1 to 200 μm. The lower limit of the average particle size is more preferably 0.5 μm, even more preferably 1 μm, particularly preferably 1.5 μm, and most preferably 2 μm. On the other hand, the upper limit of the average particle size is more preferably 100 μm, even more preferably 50 μm, particularly preferably 40 μm, and most preferably 30 μm.
[0022] [Component (C)] The anti-adhesive composition of the present invention contains an anionic surfactant as component (C), which imparts wettability and anti-adhesive properties and aids in the dispersibility of components (A) and (B) and their adhesion to unvulcanized rubber. Examples of component (C) include fatty acid salts, alkyl sulfate ester salts, polyoxyethylene alkyl sulfate salts, acyl N-methyl amino acid salts, acyl amino acid salts, polyoxyethylene alkyl ether acetate salts, succinic acid ester salts, fatty acid alkanolamide ether carboxylate salts, acyl lactate salts, polyoxyethylene fatty amine sulfate salts, fatty acid alkanolamide sulfate salts, fatty acid glyceride sulfate salts, alkylbenzene polyoxyethylene sulfate salts, olefin sulfonates, alkyl sulfosuccinate salts, alkyl ether sulfosuccinate salts, alkylbenzene sulfonates, alkyl naphthalene sulfonates, alkanesulfonates, α-sulfo fatty acid methyl ester salts, acyl isethionate salts, alkyl glycidyl ether sulfonates, alkyl sulfoacetates, alkyl ether phosphate salts, alkyl phosphate ester salts, alkyl aryl ether phosphate salts, fatty acid amide ether phosphate salts, phospholipids, and silicone-based anionic surfactants, and one or more of these may be used in combination. The salt is not particularly limited, but examples thereof include metal salts such as sodium and potassium salts; alkanolamine salts such as monoethanolamine salts, diethanolamine salts, and triethanolamine salts; and ammonium salts. Component (C) may be composed of one or more of these.
[0023] Although there are no particular limitations on component (C), it is preferable for the component (C) to contain a fatty acid salt, which tends to further improve wettability and adhesion prevention. The number of carbon atoms in the fatty acid salt is not particularly limited, but is preferably 6 to 22. The lower limit of the carbon number is more preferably 8, even more preferably 10, and particularly preferably 12. On the other hand, the upper limit of the carbon number is more preferably 20, and even more preferably 18. The fatty acid salt may be either a straight-chain type or a branched type, or may be composed of these two types. The fatty acid salt may be either a saturated fatty acid salt or an unsaturated fatty acid salt, or may be composed of these two types. If component (C) contains an unsaturated fatty acid salt, it is preferable in terms of improving wettability.
[0024] When component (C) contains a fatty acid salt, the weight ratio of the fatty acid salt in component (C) is not particularly limited, but is preferably 20 to 100% by weight, more preferably 30 to 100% by weight, even more preferably 40 to 100% by weight, particularly preferably 50 to 100% by weight, and most preferably 60 to 100% by weight. If the weight ratio is 20% by weight or more, the wettability tends to be improved.
[0025] [Other ingredients] The anti-adhesive composition of the present invention may further contain, in addition to the above-mentioned components (A) to (C), inorganic particles, a surfactant other than an anionic surfactant, a polyhydric alcohol, a water-soluble polymer, an antifoaming agent, a preservative, mineral oil, oils and fats, water, etc. (Inorganic particles) Examples of inorganic particles include, but are not limited to, carbonates such as calcium carbonate, magnesium carbonate, barium carbonate, etc.; silicates such as bentonite, clay, kaolin, talc, mica, sericite, etc.; sulfates such as calcium sulfate, barium sulfate, etc.; metal oxides such as amorphous silica, alumina, magnesium oxide, antimony trioxide, titanium oxide, white carbon, iron oxide, etc.; metal hydroxides such as aluminum hydroxide, magnesium hydroxide, iron hydroxide, etc.; red iron oxide; carbon black; graphite, etc., and one or more of these may be used in combination. When the anti-adhesive composition of the present invention contains inorganic particles, the anti-adhesive properties tend to be improved.
[0026] Inorganic particles made of silicate are preferred from the standpoint of adhesion prevention. Furthermore, inorganic particles may contain crystalline silica as an impurity. Since crystalline silica has low hydrophilicity and low dispersibility, it is preferable that the content of crystalline silica is as small as possible. Examples of crystalline silica include quartz, cristobalite, tridymite, coesite, and stachobalite. The content of crystalline silica in the inorganic particles is preferably less than 20% by weight, particularly preferably 10% by weight or less, and most preferably 5% by weight or less. If it is 20% by weight or more, the dispersibility of the inorganic particles decreases, adhesion to the rubber surface becomes uneven, and dust scattering may increase.
[0027] The average particle size of the inorganic particles is not particularly limited, but from the viewpoint of adhesion to unvulcanized rubber, it is preferably 0.01 to 200 μm, more preferably 0.03 to 100 μm, even more preferably 0.05 to 50 μm, particularly preferably 0.07 to 40 μm, and most preferably 0.1 to 30 μm.
[0028] (Polyhydric alcohol) The polyhydric alcohol is not particularly limited, but examples thereof include glycerin, 1,3-butanediol, propylene glycol, dipropylene glycol, polypropylene glycol, pentylene glycol, neopentyl glycol, hexylene glycol, polyethylene glycol, erythritol, pentaerythritol, dipentaerythritol, trimethylolethane, trimethylolpropane, ditrimethylolpropane, xylitol, sorbitol, mannitol, maltitol, maltotriose, glucose, sucrose, fructose, maltose, and the like, and one or more of these may be used in combination. When the anti-adhesive composition of the present invention contains a polyhydric alcohol, the smoothness between the unvulcanized rubbers tends to be improved.
[0029] (Water-soluble polymer) The water-soluble polymer is not particularly limited, and examples thereof include starches such as wheat starch, corn starch, potato starch, sweet potato starch, tapioca starch, wheat flour starch, oxidized starch, starch acetate, starch phosphate, carboxymethyl starch, carboxyethyl starch, hydroxyethyl starch, cationic starch, cyanoethylated starch, dialdehyde starch, and phosphorylated starch; mannan; the alginic acid is not particularly limited, and examples thereof include alginic acid, sodium alginate, propylene glycol alginate, triethanolamine alginate, and ammonium alginate; taracant gum, gum arabic, guar gum, xanthan gum, British gum, glucomannan, gellan gum, taragan gum, and the like. Examples of water-soluble polymers include natural gums such as cellulose gum, locust bean gum, carrageenan, welan gum, diutan gum, tamarind gum, tamarind seed gum, tragacanth gum, rhamsan gum, succinoglycan, karaya gum, and pectin; cellulose ethers such as methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, hydroxypropyl methyl cellulose, carboxymethyl cellulose and salts thereof, proteins such as gelatin, casein, and collagen; sodium polyacrylate; polyvinyl alcohol; polyethylene glycol; polyethylene oxide; water-soluble acrylic resins; water-soluble urethane resins; water-soluble melamine resins; water-soluble epoxy resins; water-soluble butadiene resins; and water-soluble phenolic resins, and these may be used alone or in combination of two or more. When the anti-adhesive composition of the present invention contains a water-soluble polymer, the dispersion stability of the anti-adhesive composition tends to be improved.
[0030] (Antifoaming agent) Examples of the defoaming agent include silicone-based defoaming agents such as polymethylsiloxane and polyether-modified silicone; oil-based defoaming agents such as castor oil, sesame oil, linseed oil, and animal and vegetable oils; fatty acid-based defoaming agents such as stearic acid, oleic acid, and palmitic acid; fatty acid ester-based defoaming agents such as isoamyl stearate, distearyl succinate, ethylene glycol distearate, and butyl stearate; polyoxyalkylene monohydric alcohol di-t-amylphenoxyethanol, 3-heptanol, 2-ethylhexyl ether, and the like. Examples of such defoamers include alcohol-based defoamers such as xanol; ether-based defoamers such as di-t-amylphenoxyethanol, 3-heptyl cellosolve, nonyl cellosolve, and 3-heptyl carbitol; phosphate-based defoamers such as tributyl phosphate and tris(butoxyethyl) phosphate; amine-based defoamers such as diamylamine; amide-based defoamers such as polyalkylene amide and acylate polyamine; sulfate-based defoamers such as sodium lauryl sulfate; polyoxyalkylene-based defoamers; and mineral oil.
[0031] (Preservatives) Examples of preservatives include thiazoles such as thiazole and 2-mercaptothiazole; thiocyanates such as methylene bisthiocyanate and ammonium thiocyanate; sulfimides such as o-benzoic sulfimide and phenylmercuric-o-benzoic sulfimide; alkyl dialkyl thiocarbamates such as methyl dimethyl thiocarbamate and ethyl diethyl dithiocarbamate; thiuram sulfides such as tetramethyl thiraum sulfide and tetraethyl thiraum sulfide; thiuram disulfides such as tetramethyl thiraum disulfide and tetraethyl thiraum disulfide; dithiocarbamates such as ferric diethyl dithiocarbamate and lead dimethyl dithiocarbamate; sulfamides such as o-toluenesulfonamide and benzenesulfonanilide; 1-aminonaphthyl-4-sulfonamide. aminosulfonic acids such as 1-amino-2-naphthol-4-sulfonic acid; phenols such as pentachlorophenol and o-phenylphenol and their alkali metal salts; chlorinated quinones such as tetrachloro-p-benzoquinone and 2,3-dichloro-1,4-naphthoquinone; nitro group-containing compounds such as dinitrocaprylphenyl crotonate and dinitro-o-cresol; triazines such as 1,3,5-trihydroxyethylhexahydro-1,3,5-triazine and 1,3,5-triethylhexahydro-1,3,5-triazine; organic mercury compounds such as phenylmercuric phthalate and o-hydroxyphenylmercuric chloride; amines such as p-aminoazobenzene and diphenylamine; amides such as cinnamanilide; and iodine-containing compounds such as 1,3-diiodo-2-propanol.
[0032] [Anti-adhesive composition for unvulcanized rubber and its manufacturing method] The anti-adhesive composition for unvulcanized rubber of the present invention contains the above-mentioned components (A) to (C) and satisfies the following condition 1, and is excellent in drying property and anti-adhesiveness. Condition 1: The content of component (A) and the content of component (B) satisfy the relationship represented by the following formula (I). Content of component (A) < Content of component (B) (I)
[0033] In the anti-adhesive composition of the present invention, if the contents of components (A) and (B) are equal or greater than that of component (A), the surface of component (B), which is hydrophobic and slippery, is likely to be largely covered by component (A), resulting in poor drying properties when applied to unvulcanized rubber, and insufficient adhesion prevention. By satisfying the above condition 1, the surface of component (B) is not largely covered by component (A), and the adhesion-preventive composition can achieve both drying properties and adhesion prevention properties. In the present invention, the content of component (A) and the content of component (B) are both based on weight (meaning the content weight).
[0034] The ratio (A / B) of the content of component (A) to the content of component (B) is not particularly limited, but is preferably 0.005 to 0.98. When the ratio is 0.005 or more, the adhesion prevention and drying properties tend to be improved, and when the ratio is 0.98 or less, the conformability of the coating tends to be improved. The lower limit of the ratio is more preferably 0.01, even more preferably 0.015, and particularly preferably 0.02. On the other hand, the upper limit of the ratio is more preferably 0.95, even more preferably 0.9, particularly preferably 0.8, and most preferably 0.7.
[0035] The content of component (C) relative to 100 parts by weight of component (B) is not particularly limited, but is preferably 1 to 500 parts by weight. When the content is 1 part by weight or more, the adhesion of component (B) to unvulcanized rubber tends to improve, and when the content is 500 parts by weight or less, the wettability of unvulcanized rubber tends to improve. The lower limit of the weight ratio is more preferably 5 parts by weight, even more preferably 10 parts by weight, and particularly preferably 20 parts by weight. On the other hand, the upper limit of the content is more preferably 400 parts by weight, even more preferably 350 parts by weight, and particularly preferably 300 parts by weight.
[0036] The weight percentage of component (A) in the non-volatile content of the anti-adhesive composition of the present invention is not particularly limited, but is preferably 0.5 to 49% by weight. When the weight percentage is 0.5% by weight or more, the anti-adhesive property tends to be improved, and when the weight percentage is 49% by weight or less, the conformability of the coating film tends to be improved. The lower limit of the weight percentage is more preferably 1% by weight. On the other hand, the upper limit of the weight percentage is more preferably 40% by weight, even more preferably 35% by weight, and particularly preferably 30% by weight. In the present invention, the non-volatile content of the anti-adhesive composition refers to the residue when the anti-adhesive composition is heated at 110° C. and the weight becomes constant.
[0037] The weight ratio of component (B) in the non-volatile content of the anti-adhesive composition of the present invention is not particularly limited, but is preferably 2 to 60% by weight. When the weight ratio is 2% by weight or more, anti-adhesive properties and slip properties tend to be improved, and when the weight ratio is 60% by weight or less, storage stability tends to be improved. The lower limit of the weight ratio is more preferably 5% by weight, and even more preferably 10% by weight. On the other hand, the upper limit of the weight ratio is more preferably 55% by weight, even more preferably 50% by weight, and particularly preferably 45% by weight.
[0038] The weight ratio of component (C) in the non-volatile content of the anti-adhesive composition of the present invention is not particularly limited, but is preferably 1 to 70% by weight. When the weight ratio is 1% by weight or more, the wettability to the unvulcanized rubber surface tends to improve, and when the weight ratio is 70% by weight or less, the wettability to the unvulcanized rubber surface improves and components (A) and (B) tend to adhere more to the rubber surface. The lower limit of the weight ratio is more preferably 5% by weight, even more preferably 10% by weight, and particularly preferably 20% by weight. On the other hand, the upper limit of the weight ratio is more preferably 65% by weight, even more preferably 60% by weight.
[0039] The weight proportion of the inorganic particles in the non-volatile content of the adhesion-preventive composition of the present invention is not particularly limited, but is preferably 50% by weight or less, more preferably 30% by weight or less, and even more preferably 20% by weight or less.
[0040] The total weight percentage of the components (A) to (C) in the non-volatile content of the anti-adhesive composition of the present invention is not particularly limited, but is preferably 30% by weight or more. When the weight percentage is 30% by weight or more, the adhesion of the components (A) to (C) to the surface of the unvulcanized rubber improves, and the drying property and anti-adhesive property tend to be further improved. The lower limit of the weight percentage is more preferably 40% by weight, even more preferably 50% by weight, particularly preferably 60% by weight, and most preferably 70% by weight. On the other hand, the upper limit of the weight percentage is 100% by weight.
[0041] The anti-adhesive composition of the present invention may be in the form of a liquid dispersed in water. When the anti-adhesive composition is a liquid dispersed in water, the weight ratio of water in the anti-adhesive composition is not particularly limited, but is preferably 10 to 95% by weight. When the weight ratio is within the above range, the handleability of the anti-adhesive composition tends to be improved. The lower limit of the weight ratio is more preferably 20% by weight, and even more preferably 30% by weight. On the other hand, the upper limit of the weight ratio is more preferably 90% by weight.
[0042] When the anti-adhesive composition of the present invention is in the form of a liquid dispersed in water, its pH at 20°C is not particularly limited, but in terms of achieving the effects of the present application, it is preferably 6 to 13, more preferably 7 to 12.5, even more preferably 7.5 to 12, and particularly preferably 8 to 11.5. When the anti-adhesive composition of the present invention is in the form of a liquid dispersed in water, the viscosity at 20° C. is not particularly limited, but in terms of the handleability of the anti-adhesive composition, it is preferably 5000 mPa·s or less, more preferably 3000 mPa·s or less, even more preferably 2000 mPa·s or less, and particularly preferably 1000 mPa·s or less. On the other hand, the lower limit of the viscosity is preferably 10 mPa·s, more preferably 20 mPa·s, and even more preferably 30 mPa·s. The viscosity of the anti-adhesive composition of the present invention at 20°C is measured at 20°C using a Brookfield viscometer (12 rpm).
[0043] The method for producing the anti-adhesive composition of the present invention includes, for example, a method of mixing components (A) to (C) and, if necessary, other components, etc. In the method for producing the anti-adhesive composition, the mixing order, etc. is not particularly limited, and all the components may be mixed at the same time, or each component may be mixed in order, or some components may be mixed in advance, and the remaining components or a mixture thereof may be added to the obtained mixture, mixed, and dispersed. The mixing method is not particularly limited, and can be performed using a device equipped with a very simple mechanism such as a container and a stirring blade. Examples of the mixing device include a Nauta mixer, a V-type mixer, a conical blender, a ribbon mixer, a high-speed mixer, a homomixer, a homogenizer, a colloid mill, and a line mixer.
[0044] [Method for producing anti-adhesive treated unvulcanized rubber] The method for producing an adhesion-preventive treated unvulcanized rubber of the present invention includes a treatment step of adhering the adhesion-preventive composition for unvulcanized rubber to the surface of the unvulcanized rubber. Here, the unvulcanized rubber is preferably one that has been molded. The treatment step may include a method of spraying the anti-adhesive composition, a dispersion obtained by dispersing the anti-adhesive composition in water, or a diluted solution thereof, a method of spraying the rubber with a thin stream, a method of immersing the rubber in the dispersion, etc. The method of immersing the rubber in the dispersion is preferred because the anti-adhesive composition for unvulcanized rubber can be uniformly attached. The unvulcanized rubber used in the production method of the present invention is usually in a heated state at 100 to 180°C, and the unvulcanized rubber can be cooled by immersing it in a dispersion liquid. The temperature of the dispersion liquid is not particularly limited, but is preferably 0 to 60°C. Next, a step of drying the unvulcanized rubber after the dispersion liquid is applied may be carried out. The drying method is not particularly limited, but a method of forcibly drying by blowing hot air with a hot air blower or blow heater is preferable because it is inexpensive.
[0045] When the anti-adhesive composition is diluted with water, the effective concentration of the dilution is not particularly limited, but is preferably 0.01 to 15% by weight in terms of easily exhibiting good wettability and anti-adhesiveness. If the concentration is 0.01% by weight or more, the anti-adhesiveness tends to improve, and if the concentration is 15% by weight or less, the drying property tends to improve. The lower limit of the concentration is more preferably 0.05% by weight, and even more preferably 0.1% by weight. On the other hand, the upper limit of the concentration is more preferably 12.5% by weight, and even more preferably 10% by weight. The above-mentioned effective concentration refers to the concentration of the components other than water in the dilution solution. The anti-adhesion treated unvulcanized rubber produced in this manner can be prevented from sticking to each other when it is stacked and stored until it is moved to the next process. EXAMPLES
[0046] The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to these examples. In the following examples and comparative examples, unless otherwise specified, "%" means "% by weight" and "parts" means "parts by weight." Furthermore, the evaluation of each physical property in the following examples and comparative examples was carried out as follows.
[0047] [Wettability] A NR / BR rubber test piece (natural rubber / butadiene rubber; thickness 0.5 cm x length 5 cm x width 3 cm) heated to 100°C was immersed in a diluted solution (effective concentration 3%) of the adhesion preventive composition for unvulcanized rubber and immediately pulled out. The wettability of the unvulcanized rubber surface was then evaluated. The entire surface of the unvulcanized rubber is wet: wettability is good (index is ◎) 95% or more but less than 100% of the unvulcanized rubber surface is wet: Wettability is somewhat good (index is ○) 80% to less than 95% of the unvulcanized rubber surface is wet. : Wettability is slightly poor (index is △) Less than 80% of the entire unvulcanized rubber surface is wetted. : Wettability is poor (index is ×)
[0048] [Drying] An NR / BR rubber test piece (natural rubber / butadiene rubber; 0.5 cm thick x 5 cm long x 3 cm wide) heated to 100°C was immersed in a diluted solution (effective concentration 3%) of the anti-adhesive composition for unvulcanized rubber and then immediately removed. Drying property is determined by the time it takes for the rubber surface to become completely dry except for the bottom end after it becomes wet. Drying time is 30 seconds or less: Drying is very good (index is ◎) Drying time is between 30 and 40 seconds: Drying is good (index is ○) Drying time is between 40 and 60 seconds: Drying is slightly poor (index is △) Drying time over 60 seconds: Drying is poor (indicator is ×)
[0049] [Adhesion resistance] An NR / BR test piece (natural rubber / butadiene rubber; 0.5 cm thick x 5 cm long x 3 cm wide) heated to 100°C is immersed in the anti-adhesive composition for unvulcanized rubber dispersed in water adjusted to 45°C and then immediately removed. Two immersed rubber test pieces are prepared, air-dried, stacked, and subjected to a load of 1000 kg / m 2 The specimens were left in a 40°C thermostatic chamber for 24 hours with a corresponding load applied. The specimens were then taken out of the chamber and allowed to air-cool to room temperature, after which the peel resistance (N / cm) was measured at a speed of 100 mm / min using a tensile tester. The smaller the peel resistance, the easier it is to peel off, and the higher the adhesion resistance. The evaluation criteria were as follows, with a peel resistance of 2 N / cm or less being considered a pass. Peel resistance of 1N / cm or less: Very good adhesion resistance (unvulcanized rubber can be easily peeled off from each other, the index is ◎) Peel resistance is over 1N / cm and 2N / cm or less: Good adhesion resistance (unvulcanized rubber can be peeled off from each other without any load, index is ○) Peel resistance is over 2N / cm and 3N / cm or less: poor adhesion resistance (the load when peeling unvulcanized rubber from each other is large, and adhesion resistance is low, the index is △) Peel resistance exceeds 3N / cm: Very poor adhesion resistance (rubbers are in close contact with each other and are difficult to peel off. Very poor adhesion resistance, index is ×)
[0050] Example 1 67 parts of water, carnauba wax emulsion (wax content 30% by weight, melting point of wax 83°C), 1 part of calcium caprate, 3 parts of zinc stearate, 5 parts of potassium palm fatty acid oleate, 1 part of potassium stearate, 9 parts of potassium oleate, 2 parts of mineral oil, 1 part of sodium carboxymethylcellulose, and 1 part of polydimethylsiloxane as an antifoaming agent were uniformly mixed to obtain an anti-adhesive composition for unvulcanized rubber. The content of water contained in the obtained anti-adhesive composition for unvulcanized rubber was 74 parts. Next, water was added so that the effective concentration was 3%, and the mixture was uniformly dispersed in water to obtain a diluted solution of the anti-adhesive composition for unvulcanized rubber. The obtained diluted solution was used to evaluate the drying property, wettability, and adhesion prevention. The evaluation results are shown in Table 1, and the wettability, drying property, and adhesion prevention were excellent.
[0051] (Examples 2 to 8, Comparative Examples 1 to 4) In Examples 2 to 8 and Comparative Examples 1 to 4, anti-adhesive compositions for unvulcanized rubber and dilutions were obtained and evaluated in the same manner as in Example 1, except that the compositions were changed as shown in Table 1. The results are shown in Table 1. Details of the raw materials used in the examples and comparative examples shown in Table 1 are shown below. Carnauba wax emulsion: wax content 30% by weight, wax melting point 83℃ Paraffin wax emulsion: wax content 20% by weight, wax melting point 62°C Polyethylene wax emulsion: Wax content 30% by weight, wax melting point 115℃ Modified polyethylene wax emulsion: Modified polyethylene wax with an acid value of 30 mgKOH / g, wax content of 30% by weight, melting point of wax of 134°C
[0052] [Table 1]
[0053] As can be seen from Table 1, the anti-adhesive compositions for unvulcanized rubber of Examples 1 to 8 contain wax (A), metal soap (B) and anionic surfactant (C), and satisfy condition 1 that the content of component (A) is less than the content of component (B), thereby solving the problem of the present application. On the other hand, the anti-adhesive composition not containing the wax of component (A) (Comparative Example 1), the anti-adhesive composition not containing the metal soap of component (B) (Comparative Example 2), the anti-adhesive composition not containing the anionic surfactant of component (C) (Comparative Example 3), and the anti-adhesive composition not satisfying the above condition 1 (Comparative Example 4) do not solve the problem of the present application.
Claims
1. An adhesion inhibitor composition for unvulcanized rubber comprising the following components (A) to (C): An anti-adhesive composition for unvulcanized rubber, which satisfies the following condition 1: Component (A): Wax Component (B): Metal soap Component (C): Anionic surfactant Condition 1: The content of the component (A) and the content of the component (B) satisfy the relationship represented by the following formula (I). Content of component (A) < Content of component (B) (I)
2. The adhesion inhibitor composition for unvulcanized rubber according to claim 1, wherein the total weight ratio of the components (A) to (C) to the non-volatile content of the adhesion inhibitor composition for unvulcanized rubber is 30% by weight or more.
3. The adhesion-preventive composition for unvulcanized rubber according to claim 1 or 2, wherein the weight ratio of the component (A) to the non-volatile content of the adhesion-preventive composition for unvulcanized rubber is 0.5 to 49% by weight, the weight ratio of the component (B) is 2 to 60% by weight, and the weight ratio of the component (C) is 1 to 70% by weight.
4. The adhesion inhibitor composition for unvulcanized rubber according to claim 1 or 2, wherein the component (C) comprises a fatty acid salt.
5. A method for producing adhesion-preventively treated unvulcanized rubber, comprising a step of adhering the adhesion-preventive composition for unvulcanized rubber according to claim 1 or 2 to a surface of molded unvulcanized rubber.
Citation Information
Patent Citations
Adhesion-preventive agent composition for unvulcanized rubber and method of producing adhesion-prevented unvolcanized rubber
JP2009161667A
Abhesive composition for unvulcanized rubber
WO2018030395A1